2008
DOI: 10.1007/s00894-008-0332-x
|View full text |Cite
|
Sign up to set email alerts
|

A neural networks study of quinone compounds with trypanocidal activity

Abstract: This work investigates neural network models for predicting the trypanocidal activity of 28 quinone compounds. Artificial neural networks (ANN), such as multilayer perceptrons (MLP) and Kohonen models, were employed with the aim of modeling the nonlinear relationship between quantum and molecular descriptors and trypanocidal activity. The calculated descriptors and the principal components were used as input to train neural network models to verify the behavior of the nets. The best model for both network mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Electronic and structural properties are important factors in determining the interaction between quinone compounds with trypanocidal activity and their biological receptors. ANN models could be useful in the design of novel trypanocidal quinones having improved potency [132].…”
Section: Quantitative Structure-activity Relationshipsmentioning
confidence: 99%
“…Electronic and structural properties are important factors in determining the interaction between quinone compounds with trypanocidal activity and their biological receptors. ANN models could be useful in the design of novel trypanocidal quinones having improved potency [132].…”
Section: Quantitative Structure-activity Relationshipsmentioning
confidence: 99%
“…In chemistry, the use of neural networks has further expanded into the analysis of spectral data, drug design, prediction of chemical reactivity and physical properties as well as the development of quantitative structure-activity relationship. [31][32][33][34][35][36] Some advantages of neural networks, useful for the purpose of this work, are as follows: (i) they are adaptative, i.e., they can take data and learn from it; (ii) they are essentially nonlinear; (iii) they are capable of generalization, i.e., they can correctly process information that only broadly resembles the original data training; (iv) they are fault-tolerant being capable of properly handling noisy or incomplete data.…”
Section: Introductionmentioning
confidence: 99%
“…Both obtained nonlinear models predicted the biological activity with good agreement to experimental data and the authors concluded that the employed descriptors were important to describe the main interactions between the substances and the biological target [25]. The first QSAR model for substances with affinity to vesicular monoamine transporter-2 (VMAT-2) was constructed by Zheng et al [71] that used the MLP methodology.…”
Section: Self-organizing Mapsmentioning
confidence: 89%
“…This technique was successfully applied to chemical analysis problems using atomic absorption spectrometry [60] and to obtain the near-infrared spectral calibration of complex beverage samples [61]. Besides these applications, the SOM potentialities have been shown in the modeling toxicity [62] and design of novel trypanocidal quinone compounds [25]. Other use of SOM involves the separation of compounds in training and test.…”
Section: Self-organizing Mapsmentioning
confidence: 99%
See 1 more Smart Citation